Effect of large topography on atmospheric environment in Sichuan Basin: A climate analysis based on changes in atmospheric visibility - Zhang, Lei; Guo, Xiaomei; Zhao, Tianliang; Xu, Xiangde; Zheng, Xiaobo; Li, Yueqing; Luo, Lei; Gui, Ke; Zheng, Yu; Shu, Zhuozhi (Frontiers in Earth Science, 2022)
Using 51 years (1960–2010) of observations from meteorological stations in the Sichuan-Chongqing region, including atmospheric visibility as a proxy for aerosol concentration, relative humidity, air temperature, wind speed and FNL reanalysis data (1°×1°) of air temperature, pressure and wind, and the altitude of each station, a linear trend and multivariate fitting approach was used to explore the effects of the large topography on the atmospheric environment in the Sichuan-Chongqing region. The region mainly consists of two areas: Sichuan Basin (SCB) and Western Sichuan Plateau (WSP; eastern part of the Tibetan Plateau). Visibility was relatively low in the SCB and high in the WSP, indicating the high and low levels of aerosols respectively in the SCB and the WSP. Additionally, visibility and wind speed were positively correlated within the basin (altitude below 750 m), while negatively correlated at stations above 1,500 m, such as on the WSP, indicating that the topography had an influence on the atmospheric environment of the basin. On the one hand, the vertical structures of the wind fields and the vertical profiles of latitudinal deviations in wind speed and air temperature in the basin show that the unique large topography causes a “harbour” effect on the leeward-slope of the WSP, with the SCB being a weak wind region, while the descending air currents in the upper westerlies of the basin form a huge “vault” of air. On the other hand, topographic effects can make the basin more susceptible to the formation of inversion structures near the surface and at high altitudes, thus stabilising the atmosphere. The topographic effects, which is not conducive to horizontal diffusion and convective transport of pollutants, were the most significant in winter, followed by autumn and spring.